Respuesta :

hey there!

The given expression is [tex] 25x^{2}-49y^{2}[/tex]

This can be written as [tex](5x)^{2}-(7y)^{2}[/tex]

This is in the form of [tex]a^{2}-b^{2}[/tex]

This can be written in form of (a+b)(a-b)

So now our answer is (5x-7y)(5x+7y)

Hope it helps you dear!
Have a good day <3

given:

[tex]25 {x}^{2} - 49 {y}^{2} [/tex]

solution:

[tex] {a}^{2} - {b}^{2} = (a + b)(a - b)[/tex]

[tex]a = 5x[/tex]

[tex]b = 7y[/tex]

[tex]25 {x}^{2} - 49 {y}^{2} [/tex]

[tex] = (5x - 7y) {}^{2} [/tex]

[tex] = (5x - 7y)(5x + 7y)[/tex]

hence, the correct answer is option B